Juridical Analysis of Inkracht Decision on Hadhanah Rights in Kepahiang Religious Court - Sidiq Aulia (Istinbath : Jurnal Hukum, 2024)
This study aims to analyse the inkracht decision related to hadhanah rights at the Kepahiang Religious Court and assess the legal certainty provided in the case. The focus of this study is how judges consider aspects of Islamic law and positive law in deciding post-divorce hadhanah cases. The research method used is normative juridical research with a case study approach. Data was obtained through interviews with judges, review of court decision documents, and analysis of relevant laws and regulations. The results showed that the judge's decision in the case of hadhanah rights at the Kepahiang Religious Court emphasised the aspects of the benefit of the child, but there were still challenges in the implementation of the decision, especially regarding the implementation of the father's maintenance obligations. In addition, although Islamic law and positive law have clearly regulated hadhanah, social and economic factors often affect the effectiveness of the implementation of decisions in the community. The conclusion of this study is that although the hadhanah decision in the Kepahiang Religious Court has provided legal certainty for the disputing parties, its implementation still requires supervision and a stronger law enforcement mechanism so that children's rights are protected. Therefore, an active role is needed from the legal apparatus and related institutions in ensuring the implementation of fair and equitable decisions.